Using of perfectly matched layer (PML) in compucter simulation of the high-power relativistic plasma microwave amlifier - Bogdankevich, I.L.; Rukhadze, A.A.; Tarakanov, V.P. (Вопросы атомной науки и техники, 2005)
Computer simulation of the relativistic plasma microwave amplifier was made by using code KARAT. A pure amplification regime (without accompanying generation) was achieved in such amplifier in the experiment [1]. The simulation system was made nearly the same experimental setup. The main feature of this model is a microwave absorber.